High dose Levothyroxine in combination with transcranial magnetic stimulation for the treatment of severe resistant subthreshold rapid cycling bipolar disorder; A case report - Andy Zamar; Ashma Mohamed; Christos Kouimtsidis (Annals of Psychiatry and Treatment - Peertechz Publications, 2022)
Bipolar Disorder (BD) is a common psychiatric condition. There is an overall agreement across treatment guidelines of BD type I and BD type II however, there is far less certainty regarding the treatment of subthreshold presentations including Rapid Cycling Bipolar Disorder. We present a patient with treatment-resistant rapid cycling Bipolar Disorder type I who deteriorated on Ketamine treatment but reached full remission with repetitive Transcranial magnetic stimulation, High Dose Levothyroxine, Lurasidone and Lithium Carbonate. This case highlights the previously demonstrated safety and effectiveness of the combined protocol of High Dose Levothyroxine and Transcranial Magnetic Stimulation for this population.